Shoulder and hip roll changes during 200-m Front crawl swimming - Psycharakis, S. G.; Sanders, R. H. (Medicine & Science in Sports & Exercise, 2008)
Purpose: To determine accurately the magnitude and changes in shoulder roll (SR) and hip roll (HR) throughout a 200-m maximum front crawl swim and whether SR and HR were associated with swimming velocity (V). Bilateral roll asymmetries and timing differences between SR and HR were also investigated.